Saying and doing - Wiest, Flora Emilie (My University, 1891)
Introduction: We find very many today who are always ready and willing to give advice on all subjects whether asked for it or not, and even if it is not wanted. No matter what you think about it they always know a better plan, and are offended if you do not take their advice. This is illustrated especially in case of sickness. There are a dozen or more perhaps who know just what will cure that disease because they know of someone whom it has helped or who has tried it, and you are entreated to try their remedy. Many are always ready to advice, but there are very few who would follow such advice as they themselves give. Then too, many speak on subjects which they know nothing about or which are really contrary to their own thoughts as is seen by the lives they lead. For instance; there are so many who write of the dignity of labor; the high position it should occupy in the minds of all and the reverence with which it should be looked upon. Although labor is man’s great function, his peculiar distinction, how many of those who are continually singing its praises really think this is true? It is said frequently that the laborer should be honored but do all honor him? Do any honor him? Labor is not a disgrace, it is elevating they will tell you but they do not care to place the laborer on an equal footing with themselves or even to place him on a higher level than he is at present.
Citation: Wiest, Flora Emilie. Saying and doing. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Labor; Class; Advice; Personal experience; Sociology; Theses; Manuscripts (documents)